ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI INDUSTRI KERAJINAN PATUNG KAYU DI KECAMATAN SUKAWATI - Putra, I Wayan Permana Adi; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2023)
The development of the production value of the wooden sculpture industry in Sukawati District has fluctuated from 2017-2021. The purpose of this study was to analyze the economies of scale and the factors that influence production in the wooden sculpture industry in Sukawati District. The data used is primary data and the analysis technique used is multiple linear regression analysis with the Cobb-Douglas approach. The results showed that capital, labor and technology simultaneously affected the production of the wooden sculpture industry and partially capital and labor had a positive and significant effect on the production of the wooden sculpture industry, while technology was a dummy variable stating that the production of wooden sculptures using Modern technology is higher than using traditional technology and the wooden sculpture industry in Sukawati District. is in a condition of Increasing Return to Scale. Keywords: capital, labor, technology, production